The effort to the economy growth of developing countries is directed to create an integrated zone that will motivate export, invite investors, and be a catalyst of a continuous growing and developing region. This research is to design agroestat as an integrated agricultural zone under one management based on local specific competitive horticulture with regional development approach. The research of agroestat is holistic covering the whole value-chain (farming, industry, and trading) of the reg - Handojo Kristyanto; Syamsul Maarif; Eriyatno .; Sutrisno .; Nastiti Siswi Indrasti; Tajuddin Bantacut (Forum Pasca Sarjana, 2009)
The effort to the economy growth of developing countries is directed to create an integrated zone that will motivate export, invite investors, and be a catalyst of a continuous growing and developing region.  This research is to design agroestat as an integrated agricultural zone under one management based on local specific competitive horticulture with regional development approach.  The research of agroestat is holistic covering the whole value-chain (farming, industry, and trading) of the regional, national, and international process agriculture.  Agroestat make use of a complex and complicated inter-dependency and inter-relation of multidimensional (social, culture, and economy) among sectors (agriculture, industry, and commerce).  Therefore, this research applied, soft, system methodology to design conceptual model of agroestat (soft system) and decision support system (hard system).  The study of agroestat benchmarks to three models of newly specific developed integrated region that is Perkebunan Inti Rakyat (PIR), agropolitan, and ecoindustrial park model.  The conceptual model of agroestate, consist of five individual elements which are infrastructure, district, business, funding, and management.  As a whole it describes the agroestate model.  Regionalization of agroestate is using objective and subjective approach into three (agriculture, industry, and commerce) economic zone on fair free trade competition and decentralization of government policy.  Agroestat in the smallest autonomous area of Kabupaten/Kota applying the integrity concept, needs supports of local government in indirect-subsidies (infrastructure) and regulation (spatial order).  Agroestate needs an independent, professional, commercial institution to manage agroestate.  The validation of Agroestat DSS (decision support system) has been done in Kabupaten Brebes with shallot as local competitive horticulture commodity. Key words: agroestat, agricultural region, agriculture, shallot